Баркарольний принцип композиційно-жанрової організації «Берестечка» Ліни Костенко - Саєнко, В. (Слово і Час, 2021)
У статті вперше цілісно і в синестетичному річищі (через компонент музичності — власне, баркарольний принцип поетичного творення) проаналізовано історичний роман у віршах «Берестечко» Ліни Костенко. Простежено особливості засвоєння жанру, виформування його в доробку авторки «Берестечка» — поетки особливого музичного чуття й ідіостильового заглиблення у сферу музики. Установлено, що баркарола стала однією з форм модернізації художнього мислення Ліни Костенко. У «Берестечку» поетка витворює особливу голо- сову поліфонію, в якій кожна зі змістоформ-конструктів модерного цілого (романний ліро-епос і баркарола) звучить і виокремлено, і взаємодоповнюючись, а партія героя-протагоніста зливається з «я» суб’єкта мовлення. The paper deals with a historical novel in verse by the celebrated modern Ukrainian writer Lina Kostenko, for the first time analyzing it totally in a synesthetic way — through the component of musicality (namely barcarole principle of poetic creativity). The folklore origins of barcarole in the world culture have been traced, as well as the peculiarities of the absorption of the genre by professional music and literature, especially Ukrainian. Formation of the genre in the creative work of the author of “Berestechko”, who is the poet of a special musical feeling, deserves special attention. Barcarole is one of the forms of modernity in the creative thinking of Lina Kostenko; it is a natural writer’s way of perceiving reality and transforming it into an aesthetic system of artistic work (both in poems and the novel in verse). Being inclined to poetically adopt chamber and solo musical genres, the poetess creates a special voice polyphony in “Berestechko”, where each sense construct of a modern unity, i. e. novel lyric epos and barcarole, sounds both separately and complementarily, and the part of a protagonist merges into ‘I’ of a speaker. The compositional function of barcarole in “Berestechko” is the modeling of a central character of the text. It is hetman Bohdan Khmelnytskyi, spiritually undermined by the recent defeat. The barcarole elements are used for constructing the author’s version of this failure and its consequences, which spread around Ukraine as circles on water; absorbing a soothing rhythm of a song, which can cure the soul with love; shaping the architectonics of the text in the form of ‘splashes’-’circles’ with polyfunctional titles and subtexts. In the genre structure of the novel, barcarole is essential both in the development of the theme and its stylistic implementation. In the unity of the work, one may notice ‘prelude’, the main part, and ‘postlude’, each part with its artistic sense. The images typical for a barcarole — water, boat, song, woman, love, etc. — are designed in accordance with the agrarian microcosm of the main character and its symbolic senses. Time flow, self-immersion, and love do not only spiritually heal hetman Bohdan Khmelnytskyi, but give his life a direction and endow his figure with grandeur. The neoromantic potential of barcarole and the novel in verse correspond well and join in the final coda about the unshakable courage and heroism of the Ukrainian warriors.